Investigating the compliance of ethnic relations mooc to gagné nine events of instruction / Tengku Intan Suzila T.S. …[et al.] - T.S, Tengku Intan Suzila; Omar, S.R; Ahmat, N.N; Hassan, M; M.N., Mohd Yusri (Universiti Teknologi MARA Cawangan Pahang, 2021)
Teaching and learning have witnessed a rapid development of Massive Open Online Courses (MOOC) especially during the pandemic of Covid-19. Many courses have been produced and received participation worldwide. These have generated unprecedented massive educational resources including videos, subtitles, lecture notes, quizzes etc. for teaching, and forum contents, Wiki, learning behaviour logs, homework logs etc. for learning. The problem that guides the study is the venerability towards exploitations such as incomplete dissemination of knowledge and violation of learning principles especially if monitoring activities are neglected. Thus, the present paper aims to report on the current development of MOOCs for the general studies subject (MPU) – particularly, Ethnic Relations course and explore the strengths and weaknesses as a subject in MOOC. The significance of the study is it may assist others in developing MOOC contents that suit students demand better and also manage to achieve its learning objectives based on Gagné’s Nine Events of Instruction.